2017
DOI: 10.1080/01658107.2017.1328604
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Non-arteritic Anterior Ischaemic Optic Neuropathy as the Presentation of Systemic Amyloidosis

Abstract: A 75-year-old hypertensive female with stable idiopathic intermediate uveitis presented with bilateral sequential optic neuropathy with optic disc swelling. The optic neuropathy in the first affected eye (right) was thought to be due to non-arteritic anterior ischaemic optic neuropathy (NAION). Asymptomatic left optic disc swelling was found at routine review 2 months later, and a diagnosis of giant cell arteritis (GCA) was sought. Temporal artery duplex ultrasound showed the "halo sign," but a subsequent temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
(14 reference statements)
1
7
0
Order By: Relevance
“…In our study, a high sensitivity of US reaching 81.98% (95% CI 73.55-88.63%) and specificity of 99.43% (95% CI 96.88-99.99%) was demonstrated. Although our study confirmed a high specificity of US for the diagnosis of GCA, it must be kept in mind that the halo sign has been described in patients with TA involvement due to other diseases, including anti-neutrophil cytoplasm antibodies (ANCA)-associated vasculitis, amyloidosis, and neoplasms, therefore, the US findings must in all cases be correlated with the clinical scenario [18][19][20]. The early referral of patients with suspected GCA to a FTA clinic is critical to prevent acute complications, such as permanent visual loss [6,7,21].…”
Section: Discussionsupporting
confidence: 74%
“…In our study, a high sensitivity of US reaching 81.98% (95% CI 73.55-88.63%) and specificity of 99.43% (95% CI 96.88-99.99%) was demonstrated. Although our study confirmed a high specificity of US for the diagnosis of GCA, it must be kept in mind that the halo sign has been described in patients with TA involvement due to other diseases, including anti-neutrophil cytoplasm antibodies (ANCA)-associated vasculitis, amyloidosis, and neoplasms, therefore, the US findings must in all cases be correlated with the clinical scenario [18][19][20]. The early referral of patients with suspected GCA to a FTA clinic is critical to prevent acute complications, such as permanent visual loss [6,7,21].…”
Section: Discussionsupporting
confidence: 74%
“…The final cases included, representing 32 patients over 50 years of age, are summarized in Table 1. The most common finding (19 cases) in the temporal artery biopsy from these reports was the deposition of eosinophilic material with positive staining for Congo-red, indicating amyloidosis 9–23 . In some cases, the amyloid was not readily apparent on the temporal artery biopsy, and only after a second review with Congo-red staining was the amyloid obvious, 19 and in other cases there were findings suggestive of both GCA and amyloid deposition from multiple myeloma, indicating that the two diagnoses can sometimes co-exist 9,21 .…”
Section: Resultsmentioning
confidence: 92%
“…Optic neuropathy or other optic nerve involvement has not been previously reported in association with gelsolin amyloidosis, however, bilateral consecutive anterior ischemic optic neuropathy has been documented in patients with the sporadic light-chain amyloidosis [ 21 , 22 ]. The possible amyloid mechanisms underlying optic nerve edema include direct optic nerve infiltration with amyloid or amyloid deposition in the arterial walls perfusing the optic nerve, causing stenosis and reduced adaptability to systemic blood pressure changes.…”
Section: Discussionmentioning
confidence: 99%